Acute Phase Effect of Memantine Hydrochloride in Experimental Peripheral Nerve Injury - Hakan AK; Iskender Samet Daltaban; Sevilay Vural (Indian Journal of Neurosurgery)
Aim In this experimental study, we aimed to investigate possible healing effects of memantine hydrochloride, an N-methyl-d-aspartate (NMDA) antagonist, with clinical, biochemical, and histopathologic methods on acute peripheral nerve injury (PNI). Material and Method Forty-eight adult Wistar albino rats were divided into four groups (n = 12). The groups were arranged as sham-operated group (group 1), acute compression model group (group 2), trauma + low-dose memantine group (group 3), and trauma + high-dose memantine group (group 4). Memantine was administered intraperitoneally for 7 days. Subjects were sacrificed after the measurement of the sciatic nerve function index (SNFI) on the eighth day. Cyclooxygenase 2 (COX-2) and tumor necrosis factor-α (TNF-α) levels were measured in nerve tissues. Histopathologic evaluation was performed by electron microscopy. Results The mean sciatic function index (SFI) scores of groups 1 to 4 were +3.27 (standard deviation [SD] ±4.66),–18.2 (SD = ±11.7),–8.5 (SD = ±7.5), and–2.5 (SD = ±9), respectively. The mean COX-2 values were 0.98 ng/mL (SD = ±0.51), 1.89 ng/mL (SD = ±0.22), 1.39 ng/mL (SD = ±0.36), and 1.35 ng/mL (SD = ±0.59), respectively. TNF-α values were 0.09 pg/mL (SD = ±0.23), 1 pg/mL (SD = ±0.96), 0.46 pg/mL (SD = ±0.55), and 0.48 pg/mL (SD = ±0.78), respectively. Group 1 showed normal histologic findings. Group 2 showed marked edema particularly in large-diameter myelins. Myelin configurations were detected in large myelinated axons in group 3. The number of mast cells in endoneurium was high in group 4. Conclusion The efficacy of memantine in the acute phase of PNI appears to be significant according to the SNFI and biochemical tests. However, histologic findings suggest that high doses of memantine have a negative effect on PNI.